New Testament Greek manuscripts : Matthew varient readings arranged in horizontal lines against Codex Vaticanus - Swanson, Reuben Joseph (Sheffield, UK Sheffield Academic, 1995)
Includes bibliographical references.
Keywords: Bible. N.T. Matthew -- Greek Texts; Bible. N.T. Matthew -- Codex Vaticanus